Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additive and production method

By combining waste desulfurization agent with surfactant, lignin modifier and reinforcement, a highly dispersible rubber and plastic additive is formed, which solves the problem of resource waste in waste desulfurization agent treatment and achieves efficient regeneration of rubber and plastic materials Improved utilization and wear resistance.

CN118221999BActive Publication Date: 2024-12-13TIANJIN SIYANG NEW ENERGY TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202410618993.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-18
Publication Date
2024-12-13
Estimated Expiration
2044-05-18

AI Technical Summary

Technical Problem

In the prior art, waste desulfurization agent treatment in the petroleum and petrochemical industry is mainly carried out through incineration and landfill, resulting in waste of resources and high treatment costs, and failing to achieve effective resource recycling.

Method used

Using ultra-fine, high-dispersed self-recycling and recycling functional rubber and plastic additives, the waste desulfurization agent is combined with surfactant, lignin modifier and reinforcement agent to form rubber and plastic with high dispersion and self-healing properties. Additives, used in rubber and plastic materials to improve their mechanical properties and wear resistance.

Benefits of technology

It realizes efficient recycling and utilization of waste desulfurizer, reduces resource waste and treatment costs, and improves the wear resistance and self-repair ability of rubber and plastic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118221999B_ABST
    Figure CN118221999B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of regeneration and circulation technology, and specifically discloses a functional rubber and plastic additive for ultrafine high dispersion self-regeneration and recycling, wherein the raw materials include: waste desulfurizer, surfactant, lignin modifier, and reinforcing agent; the mass ratio of waste desulfurizer, surfactant, lignin modifier, and reinforcing agent is 100:5-15:10-20:5-10. The present invention discloses a production method of the above-mentioned ultrafine high dispersion self-regeneration and recycling functional rubber and plastic additive, comprising the following steps: adding waste desulfurizer, surfactant and water to a reactor, heating to 70-90°C, maintaining the pressure of the reactor to 0.8-1.2MPa, and keeping the temperature and pressure for 110-130min; then adding a lignin modifier, and continuing to keep the temperature and pressure for 3.5-4.5h; then adding a reinforcing agent and mixing evenly. The present invention discloses a method for using the above-mentioned ultrafine high dispersion self-regeneration and recycling functional rubber and plastic additive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of regeneration and recycling technology, and in particular to an ultrafine and highly dispersed self-regeneration and recycling functional rubber and plastic additive and a production method and a use method thereof. Background Art

[0002] In the field of gas purification in the petroleum and petrochemical industries, such as natural gas purification and factory tail gas, desulfurizers are required to remove hydrogen sulfide gas. Generally, metal iron oxide desulfurizers are used for dry desulfurization. Hydrogen sulfide and elemental sulfur can react with the active metal oxides in the desulfurizer to generate sulfides or sulfates, achieving the purpose of purifying and desulfurizing natural gas or industrial tail gas, preventing corrosion, and meeting emission standards or entering industrial pipelines.

[0003] The main pollutants in the desulfurization waste generated by natural gas desulfurization come from impurities that may be brought in by petroleum, a small amount of condensate oil, the desulfurizer itself and the desulfurization reaction. The desulfurization reaction product is metal sulfide. The waste desulfurizer is not flammable, reactive, corrosive, leaching toxic, acute toxic, and the toxicity content does not exceed the standard. The conclusion is that it is general industrial solid waste. The amount of waste desulfurizer collected at close range reaches 10,000 tons each year. The current treatment process is landfill after calcination, which does not achieve effective resource recycling and causes resource waste.

[0004] Waste metal oxide desulfurizers are generally incinerated and then landfilled. Incineration consumes energy, and waste gas is generated during the incineration process, which has a high treatment cost. After incineration, it needs to be landfilled as general industrial solid waste, occupying land and human resources. At the same time, with the rapid development of social economy, our lives are inseparable from various rubber and plastic products, but waste rubber and plastic materials are not fully utilized, resulting in waste rubber and plastic products bringing serious environmental resource waste to our country. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an ultra-fine, highly dispersed, self-regenerating and recycling functional rubber and plastic additive and a production method and a use method thereof.

[0006] The raw materials of the ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives include: waste desulfurizer, surfactant, lignin modifier, and reinforcing agent; the mass ratio of the waste desulfurizer, surfactant, lignin modifier, and reinforcing agent is 100:5-15:10-20:5-10.

[0007] Preferably, the waste desulfurizing agent is obtained by using a metal iron oxide type desulfurizing agent to carry out gas desulfurization and purification.

[0008] Preferably, the sulfur content of the metal iron oxide type desulfurizer is 15-20%; the metal iron oxide type desulfurizer comprises 25-35% calcium sulfate, 2-3% magnesium oxide, 2-5% silicon dioxide, and the balance is iron oxide.

[0009] The desulfurization reaction of the metal iron oxide type desulfurizer is as follows:

[0010] MO+H2S==MS+H2O (where M represents metal)

[0011] The specific reactions are as follows:

[0012] 2FeOOH+3H 2 S → Fe 2 S 3 +4H 2 O

[0013] Fe 2 S 3 → FeS+FeS 2

[0014] Ca 2 Fe 2 O 5 + H 2 S → Fe 7 S8 + S+ Ca 2 Fe 2 S 2 O 3 + FeS (calcium ferrite removes hydrogen sulfide)

[0015] Fe 2 O 3 + H 2 S → FeS+ S+ H 2 O↑ (iron oxide removes hydrogen sulfide)

[0016] MgO +H 2 S = MgS + H 2 O (magnesium oxide removes hydrogen sulfide)

[0017] CaSO 4 + H 2 S → CaS+H 2 SO 4

[0018] Preferably, the waste desulfurizing agent includes: ferrous sulfide, magnesium sulfide, calcium sulfide, elemental sulfur,

[0019] Silicon dioxide.

[0020] Ferrous sulfide is a dark brown hexagonal crystal that is insoluble in water; magnesium sulfide is an inorganic substance with the chemical formula MgS, white or reddish brown hexagonal crystals or powder, and calcium sulfide is a white to light yellow solid. Calcium sulfide is widely used in the rubber industry and leather industry as an additive for rubber vulcanization accelerators and calcium sulfide activators. It can also be used as a mineral beneficiation agent. Elemental sulfur is a light yellow crystal, commonly known as sulfur, which is insoluble in water and has a higher density than water. It is itself a product used in rubber vulcanization.

[0021] The metal sulfide produced by the reaction of metal oxides and hydrogen sulfide has stable properties and can be modified and used as a filler in the rubber and plastic industry.

[0022] Preferably, the surfactant is carboxymethyl cellulose.

[0023] Sodium carboxymethyl cellulose (CMC) belongs to anionic cellulose ethers, and its appearance is white or slightly yellow flocculent fiber powder or white powder, which is odorless, tasteless and non-toxic. It is easily soluble in cold or hot water to form a transparent solution with a certain viscosity. Its solution is neutral or slightly alkaline, insoluble in organic solvents such as ethanol, ether, isopropanol, acetone, etc., but soluble in ethanol or acetone solution containing 60% water.

[0024] Sodium carboxymethyl cellulose is hygroscopic, stable to light and heat, and its viscosity decreases with increasing temperature. The solution is stable at pH 2-10, solids precipitate when the pH is lower than 2, and the viscosity decreases when the pH is higher than 10. The color change temperature is 227°C, the carbonization temperature is 252°C, and the surface tension of a 2% aqueous solution is 71mn / n.

[0025] Preferably, the lignin modifier is lignin.

[0026] Lignin is classified according to its structure into: guaiacyl lignin, referred to as G lignin; guaiacyl-syringyl lignin, referred to as GS lignin. Coniferous wood lignin is mainly composed of guaiacyl propane, which belongs to G lignin. Broadleaf wood lignin is composed of guaiacyl propane and syringyl propane, which belongs to GS lignin. In addition to guaiacyl propane and syringyl propane, grass lignin also contains a large amount of p-hydroxyphenyl propane, which is called GSH lignin. In addition to guaiacyl propane, stressed wood lignin also contains a considerable amount of p-hydroxyphenyl propane, which is called GH lignin.

[0027] The distribution of lignin in plants is uneven. The content and structure of lignin vary with tree species, tree age, and sampling site. According to ultraviolet microscopy and scanning electron microscope-energy analyzer (SEM-EDXA), the lignin concentrations in the intercellular layer and cell corners of needles, broad-leaved wood, and various cells of the Poaceae family are much higher than those in the secondary wall, among which the concentration is highest in the cell corners. Since the volume of the secondary wall is much larger than that of the intercellular layer and cell corners, about 2 / 3 of the lignin in wood and Poaceae is distributed in the secondary wall. The types of lignin in different types of cells of broad-leaved wood are different. The lignin in wood fibers is mainly composed of syringyl propane, while the lignin in the vascular unit is mainly composed of guaiacyl lignin.

[0028] According to the principle of lignin separation, it can be divided into two categories: ① dissolving the high polysaccharides in plants and retaining the lignin residue; ② dissolving lignin and leaving the high polysaccharides. The lignins separated by the former method include sulfate lignin, hydrochloride lignin and periodate lignin, etc.; the latter includes ground wood lignin (abbreviated as MWL), cellulose enzymatic lignin (abbreviated as CEL), dioxane lignin, etc., and lignin sulfonic acid, alkali lignin and sulfate lignin related to the pulp and paper industry also belong to this category. Based on the activity of lignin naturally present in plants, the complexity of its structure and the intricate relationship with high polysaccharides, it has not been possible to separate lignin that fully represents the lignin in plants. Lignins separated by mild methods such as MWL and CEL are often used in the study of lignin structure.

[0029] Lignin is mainly composed of three elements: carbon, hydrogen, and oxygen. In addition to the above elements, Gramineae lignin also contains a small amount of nitrogen. The main functional groups of lignin are methoxy, hydroxyl, and carbonyl. Methoxy is a characteristic functional group of lignin. It exists on the benzene ring of the phenylpropane structural unit. The methoxy group in coniferous and broad-leaved wood lignin is 14-16% and 17-22% respectively. The hydroxyl groups in lignin include phenolic hydroxyl groups on the benzene ring and alcoholic hydroxyl groups on the side chain. Carbonyl groups exist on the side chains of the structural units. Gramineae lignin structural units also have carboxyl bonds on their side chains. It varies with the source of lignin, separation, and purification methods. The color of separated lignin ranges from light cream to dark brown. It is optically inactive. The refractive index is 1.61. The density is 1.25-1.40 g / cm2. The molecular weight ranges from several hundred to several hundred thousand, with polydispersity. The molecular weight of wood groundwood lignin is 10000-20000, and that of grass groundwood lignin is 7000-9000. The molecular shape is nearly spherical or blocky. It is insoluble in commonly used neutral organic reagents. Lignin is thermoplastic, and its softening temperature is related to the molecular weight and moisture content of lignin. The softening temperature of dry separated lignin is generally 120-200℃. The thermoplasticity of lignin is closely related to pulping, papermaking and wood processing industries. Lignin can undergo side chain reactions and selective reactions of aromatic nuclei. Side chain reactions are mostly related to active benzyl alcohol, alkyl ether bonds and aromatic ether bonds. Halogenation and nitration reactions mainly occur on aromatic nuclei. Reactions related to lignin modification include formylation, cyanoethylation, phenolization and graft copolymerization. The chemical reaction of lignin is particularly important for pulping and papermaking. Lignin undergoes nucleophilic reactions with sodium hydroxide, sodium sulfide and sulfite in the pulping process, and various electrophilic and nucleophilic reactions with molecular chlorine, chlorine dioxide, oxygen, hypochlorite and hydrogen peroxide in bleaching. Polycondensation reactions also occur in acidic and alkaline media at high temperatures. Lignin can undergo color development reactions with aliphatic compounds, phenols, aromatic amines, heterocyclic compounds and inorganic compounds. The color development reaction of lignin is closely related to the identification, classification and distribution of lignin and the quantification of specific structural groups.

[0030] In addition to being used as a fuel or retained in pulp to produce pulp with high lignin content, lignin can be used as a dye in its polymer form; a dispersant for oil wells, carbon black, cement, concrete, etc.; an emulsifier for asphalt, wax and fat; an adhesive for animal feed, graphite, iron ore, coal bricks; a water treatment agent, an industrial detergent, an anticorrosive agent, and a trace nutrient for agriculture. It also has application value as a rubber reinforcing agent, an antioxidant, a controlled pesticide, and a phenolic resin substitute. The low molecular weight chemical reagents prepared from lignin mainly include vanillin, dimethyl sulfide, and dimethyl sulfoxide. Industrial lignin is abundant in source, low in price, and non-toxic to humans and animals. Lignin has broad prospects for utilization.

[0031] Preferably, the lignin modifier is activated lignin; the activated lignin is prepared by the following operation: the carboxyl-terminated polyamidoamine and lignin are uniformly mixed, stirred at 120-140° C. for 5-15 minutes, cooled to room temperature, and crushed.

[0032] The polar functional groups of the above-mentioned lignin can combine with the terminal carboxyl polyamide amine through hydrogen bonding to form a dendritic structure on the surface of lignin, which not only promotes the extremely high dispersion uniformity of the waste desulfurizer, but its surface carboxyl group can form a coordination bond with the waste desulfurizer. When it is used in rubber and plastic materials, it can not only enhance the tensile strength and tearing properties, but also give the material self-healing properties.

[0033] More preferably, the mass ratio of the carboxyl-terminated polyamidoamine to the lignin is 1-2:5-10.

[0034] Preferably, the reinforcing agent is at least one of carbon black, white carbon black, clay, kaolin and calcium carbonate.

[0035] Carbon black is a kind of amorphous carbon. It is a light, loose and extremely fine black powder with a very large specific surface area ranging from 10-3000m 2 / g, is the product of incomplete combustion or thermal decomposition of organic matter (natural gas, heavy oil, fuel oil, etc.) under insufficient air conditions. Specific gravity 1.8-2.1. Made from natural gas is called "gas black", made from oil is called "lamp black", and made from acetylene is called "acetylene black". In addition, there are "tank black" and "furnace black". According to the properties of carbon black, there are "reinforcement carbon black", "conductive carbon black", "wear-resistant carbon black", etc. It can be used as a black dye, used in the manufacture of Chinese ink, printing ink, paint, etc., and is also used as a reinforcing agent for rubber.

[0036] Carbon black has a reinforcing effect on rubber, and has since gradually become an indispensable raw material for the rubber industry. Currently, the raw material consumption of the world's rubber industry ranks first in raw rubber, and the second is carbon black; in other words, carbon black has become the rubber compounding agent with the largest consumption. The consumption of carbon black generally accounts for 40-50% of the rubber consumption.

[0037] Carbon black for rubber - Carbon black for rubber was originally classified by particle size, but later changed to classification by nitrogen surface area. In addition, factors such as the vulcanization speed and structure of carbon black pigments are also taken into account when naming, and it consists of 4 systems. The first English letter represents the vulcanization speed of the rubber compound, with N representing normal vulcanization speed and S representing slow vulcanization speed. The following 3 are Arabic numerals. The first number represents the range of carbon black nitrogen surface area, which is listed as 0-9 levels. The second and third numbers are assigned by the D24.41 Committee of the American Society for Testing and Materials responsible for carbon black and terminology, reflecting different structural degrees, that is, the approximate high and low structures of carbon black, which are determined by a certain degree of arbitrariness. The larger the number, the higher the structure.

[0038] The greater the carbon black filling amount, the greater the density of the dispersed carbon black particles or carbon black particle aggregates, the smaller the average distance between the particles, the higher the probability of mutual contact, and the more conductive paths formed by the carbon black particles or carbon black particle aggregates. The greater the polarity of the blending system composed of polymers and carbon black of different polarities, the greater the critical volume fraction of carbon black, which means that the conductivity of the system decreases, because the surface of carbon black contains strong polar groups, the matrix has large polarity, and the effect is enhanced. At this time, the strength increases, but it hinders the aggregation of the conductive particles themselves, resulting in poor conductivity. However, in the blending system composed of multi-component matrix resin and carbon black, due to the different polarities of different matrices, the filling of carbon black will produce segregation. At this time, the conductive performance depends on the concentration and distribution state of carbon black particles in the segregation phase, and also depends on the proportion of polymers in the segregation phase.

[0039] Preferably, the reinforcing agent is prepared by the following operation: carbon black N234 and polyaspartic acid are mixed and ball-milled, mixed with polyoxyethylene lauryl ether, added into water, stirred for 10-30 minutes, filtered, washed with water, vacuum dried, and crushed.

[0040] The present invention uses polyaspartic acid and carbon black for ball milling, which can not only effectively break up carbon black agglomerates, but also polyaspartic acid can be combined with the surface of carbon black to effectively enhance its steric hindrance, and can form hydrogen bonds with the aforementioned activated lignin, which can further improve the wear resistance and achieve a dual self-repair effect.

[0041] More preferably, the mass ratio of carbon black N234, polyaspartic acid and polyoxyethylene lauryl ether is 10-20:1-2:0.1-1.

[0042] The above-mentioned method for producing ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives includes the following steps: adding waste desulfurizer, surfactant and water into a reactor, heating to 70-90°C, maintaining the pressure of the reactor at 0.8-1.2MPa, and keeping the temperature and pressure for 110-130 minutes; then adding lignin modifier, and continuing to keep the temperature and pressure for 3.5-4.5 hours; then adding reinforcing agent and mixing evenly.

[0043] Preferably, the particle size of the spent desulfurizing agent is 20-50 μm, and the smaller the particle size, the easier it is to modify.

[0044] The present invention adopts a surfactant (carboxymethyl cellulose) to emulsify the waste desulfurizer fine powder, so that the surfactant can well wet and adsorb the waste desulfurizer, and then lignin or activated lignin is added to modify the activity of the waste desulfurizer particles, and the emulsified waste desulfurizer fine particles are modified. The water in the reaction can be recycled and no wastewater or waste gas is generated.

[0045] The obtained functional rubber and plastic additive has good compatibility with the rubber and plastic material matrix, thereby greatly improving its dispersibility in the rubber and plastic material and avoiding the aggregation and heterogeneity of the waste desulfurizer particles in the rubber and plastic material.

[0046] The method for using the ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additive is to add the ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additive into the rubber and plastic polymer material and mix them evenly. The mass ratio of the ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additive to the rubber and plastic polymer material is 15-20:100.

[0047] According to the design requirements of the plasticity and hardness of the rubber and plastic materials, the usage ratio of the functional rubber and plastic additive obtained in the present invention is adjusted, generally accounting for 15-20% of the rubber and plastic raw materials.

[0048] The application scope of the functional rubber and plastic additive obtained by the present invention can be the field of rubber and plastic products, cement construction industry, mining field, electronic device field, aerospace, etc. According to the test, the functional rubber and plastic additive obtained by the present invention can significantly improve the wear resistance of rubber and plastic materials by adding them into the rubber and plastic materials, and can be used for low-speed wear-resistant tires of agricultural machinery and tools, suitcase rollers, low-speed wear-resistant conveyor belts and rollers of mining machinery, stadium runways and road pavement materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is a comparison chart of tensile strength and elongation at break of the control group and the rubber material obtained by adding the functional rubber and plastic additives obtained in Example 5, Example 6, Example 7, and Example 10 into natural rubber.

[0050] Figure 2 This is a comparison chart of the tear strength and DIN abrasion of the control group and the rubber material obtained by adding the functional rubber and plastic additives obtained in Example 5, Example 6, Example 7, and Example 10 into natural rubber.

[0051] Figure 3 This is a comparison chart of the anti-slip coefficients of rubber materials obtained by adding the functional rubber and plastic additives obtained in Example 5, Example 6, Example 7, and Example 10 to natural rubber.

[0052] Figure 4 This is a comparison chart of the impedance of the coating obtained by adding the functional rubber and plastic additives obtained in Example 5, Example 6, Example 7, and Example 10 to the epoxy resin after scratch treatment in the first 6 hours. DETAILED DESCRIPTION

[0053] The present invention will be further explained below in conjunction with specific embodiments.

[0054] The waste desulfurizer used below is obtained by using a metal iron oxide type desulfurizer (sulfur content is 18%) to desulfurize and purify the gas. The metal iron oxide type desulfurizer includes by mass percentage: 30% calcium sulfate, 2.7% magnesium oxide, 3.4% silicon dioxide, and the balance is iron oxide. Example 1

[0055] Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives, the raw materials of which include: 100kg of waste desulfurizer, 5kg of carboxymethyl cellulose, 10kg of lignin, and 5kg of carbon black N234.

[0056] The above-mentioned method for producing ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives includes the following steps: using an ultrafine grinder to mechanically grind the waste desulfurizer to a particle size of 20-50 μm, then adding it to a reactor with carboxymethyl cellulose and water, heating it to 70°C, maintaining the pressure of the reactor at 0.8 MPa, and keeping it warm and under pressure for 110 minutes; then adding lignin, and continuing to keep it warm and under pressure for 3.5 hours; then adding carbon black N234 and mixing evenly. Example 2

[0057] Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives, the raw materials of which include: 100kg of waste desulfurizer, 15kg of carboxymethyl cellulose, 20kg of lignin, and 10kg of carbon black N234.

[0058] The above-mentioned method for producing ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives includes the following steps: using an ultrafine grinder to mechanically grind the waste desulfurizer to a particle size of 20-50 μm, then adding it to a reactor with carboxymethyl cellulose and water, heating it to 90°C, maintaining the pressure of the reactor at 1.2 MPa, and keeping it warm and under pressure for 130 minutes; then adding lignin, and continuing to keep it warm and under pressure for 4.5 hours; then adding carbon black N234 and mixing evenly. Example 3

[0059] Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives, whose raw materials include: 100kg of waste desulfurizer, 8kg of carboxymethyl cellulose, 17kg of lignin, and 7kg of carbon black N234.

[0060] The above-mentioned method for producing ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives includes the following steps: using an ultrafine grinder to mechanically grind the waste desulfurizer to a particle size of 20-50 μm, then adding it to a reactor with carboxymethyl cellulose and water, heating it to 85°C, maintaining the pressure of the reactor at 0.9 MPa, and keeping it warm and under pressure for 125 minutes; then adding lignin, and continuing to keep it warm and under pressure for 3.8 hours; then adding carbon black N234 and mixing evenly. Example 4

[0061] Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives, whose raw materials include: 100kg of waste desulfurizer, 12kg of carboxymethyl cellulose, 13kg of lignin, and 9kg of carbon black N234.

[0062] The above-mentioned method for producing ultrafine, highly dispersed, self-regenerating and recycling functional rubber and plastic additives includes the following steps: using an ultrafine grinder to mechanically grind the waste desulfurizer to a particle size of 20-50 μm, then adding it to a reactor with carboxymethyl cellulose and water, heating it to 75°C, maintaining the pressure of the reactor at 1.1 MPa, and keeping it warm and under pressure for 115 minutes; then adding lignin, and continuing to keep it warm and under pressure for 4.2 hours; then adding carbon black N234 and mixing evenly. Example 5

[0063] Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives, whose raw materials include: 100kg of waste desulfurizer, 10kg of carboxymethyl cellulose, 15kg of lignin, and 8kg of carbon black N234.

[0064] The above-mentioned method for producing ultrafine, highly dispersed, self-regenerating and recycling functional rubber and plastic additives comprises the following steps: using an ultrafine grinder to mechanically grind the waste desulfurizer to a particle size of 20-50 μm, then adding it into a reactor with carboxymethyl cellulose and water, heating it to 80°C, maintaining the reactor pressure at 1 MPa, and keeping the temperature and pressure for 120 minutes; then adding lignin, and continuing to keep the temperature and pressure for 4 hours; then adding carbon black N234 and mixing evenly. Example 6

[0065] Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives, whose raw materials include: 100kg of waste desulfurizer, 10kg of carboxymethyl cellulose, 15kg of lignin, and 8kg of reinforcing agent.

[0066] The reinforcing agent was prepared by the following operation: 15 kg of carbon black N234 and 1.5 kg of polyaspartic acid were mixed and ball-milled for 15 minutes, mixed with 0.5 kg of polyoxyethylene lauryl ether and added into 80 kg of water, stirred at a speed of 800 r / min for 20 minutes, filtered, washed with deionized water, vacuum dried, and crushed.

[0067] The above-mentioned method for producing ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives includes the following steps: using an ultrafine grinder to mechanically grind the waste desulfurizer to a particle size of 20-50 μm, then adding it to a reactor with carboxymethyl cellulose and water, heating it to 80°C, maintaining the pressure of the reactor at 1 MPa, and keeping it warm and under pressure for 120 minutes; then adding lignin, and continuing to keep it warm and under pressure for 4 hours; then adding a reinforcing agent and mixing evenly. Example 7

[0068] Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives, whose raw materials include: 100kg of waste desulfurizer, 10kg of carboxymethyl cellulose, 15kg of activated lignin, and 8kg of carbon black N234.

[0069] The activated lignin was prepared by the following operation: 1.5 kg of carboxyl-terminated polyamidoamine and 8 kg of lignin were uniformly mixed, stirred at a temperature of 130° C. for 10 min, cooled to room temperature, and crushed.

[0070] The above-mentioned method for producing ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives includes the following steps: using an ultrafine grinder to mechanically grind the waste desulfurizer to a particle size of 20-50 μm, then adding it to a reactor with carboxymethyl cellulose and water, heating it to 80°C, maintaining the pressure of the reactor at 1 MPa, and keeping it warm and under pressure for 120 minutes; then adding activated lignin, and continuing to keep it warm and under pressure for 4 hours; then adding carbon black N234 and mixing evenly. Example 8

[0071] Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives, whose raw materials include: 100kg of waste desulfurizer, 10kg of carboxymethyl cellulose, 15kg of activated lignin, and 8kg of reinforcing agent.

[0072] The activated lignin is prepared by the following operation: 1 kg of carboxyl-terminated polyamidoamine and 10 kg of lignin are uniformly mixed, stirred at a temperature of 120° C. for 15 min, cooled to room temperature, and crushed.

[0073] The reinforcing agent was prepared by the following operation: 10 kg of carbon black N234 and 2 kg of polyaspartic acid were mixed and ball-milled for 10 min, mixed with 1 kg of polyoxyethylene lauryl ether and added into 50 kg of water, stirred at a speed of 1200 r / min for 10 min, filtered, washed with deionized water, vacuum dried and crushed.

[0074] The above-mentioned method for producing ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives includes the following steps: using an ultrafine grinder to mechanically grind the waste desulfurizer to a particle size of 20-50 μm, then adding it to a reactor with carboxymethyl cellulose and water, heating it to 80°C, maintaining the pressure of the reactor at 1 MPa, and keeping it warm and under pressure for 120 minutes; then adding activated lignin, and continuing to keep it warm and under pressure for 4 hours; then adding a reinforcing agent and mixing evenly. Example 9

[0075] Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives, whose raw materials include: 100kg of waste desulfurizer, 10kg of carboxymethyl cellulose, 15kg of activated lignin, and 8kg of reinforcing agent.

[0076] The activated lignin is prepared by the following operation: 2 kg of carboxyl-terminated polyamidoamine and 5 kg of lignin are mixed evenly, stirred at a temperature of 140° C. for 5 minutes, cooled to room temperature, and crushed.

[0077] The reinforcing agent was prepared by the following operation: 20 kg of carbon black N234 and 1 kg of polyaspartic acid were mixed and ball-milled for 20 min, mixed with 0.1 kg of polyoxyethylene lauryl ether and added into 100 kg of water, stirred at a speed of 500 r / min for 30 min, filtered, washed with deionized water, vacuum dried, and crushed.

[0078] The above-mentioned method for producing ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives includes the following steps: using an ultrafine grinder to mechanically grind the waste desulfurizer to a particle size of 20-50 μm, then adding it to a reactor with carboxymethyl cellulose and water, heating it to 80°C, maintaining the pressure of the reactor at 1 MPa, and keeping it warm and under pressure for 120 minutes; then adding activated lignin, and continuing to keep it warm and under pressure for 4 hours; then adding a reinforcing agent and mixing evenly. Example 10

[0079] Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives, whose raw materials include: 100kg of waste desulfurizer, 10kg of carboxymethyl cellulose, 15kg of activated lignin, and 8kg of reinforcing agent.

[0080] The activated lignin was prepared by the following operation: 1.5 kg of carboxyl-terminated polyamidoamine and 8 kg of lignin were uniformly mixed, stirred at a temperature of 130° C. for 10 min, cooled to room temperature, and crushed.

[0081] The reinforcing agent was prepared by the following operation: 15 kg of carbon black N234 and 1.5 kg of polyaspartic acid were mixed and ball-milled for 15 minutes, mixed with 0.5 kg of polyoxyethylene lauryl ether and added into 80 kg of water, stirred at a speed of 800 r / min for 20 minutes, filtered, washed with deionized water, vacuum dried, and crushed.

[0082] The above-mentioned method for producing ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives includes the following steps: using an ultrafine grinder to mechanically grind the waste desulfurizer to a particle size of 20-50 μm, then adding it to a reactor with carboxymethyl cellulose and water, heating it to 80°C, maintaining the pressure of the reactor at 1 MPa, and keeping it warm and under pressure for 120 minutes; then adding activated lignin, and continuing to keep it warm and under pressure for 4 hours; then adding a reinforcing agent and mixing evenly.

[0083] The functional rubber and plastic additives obtained in Example 5, Example 6, Example 7 and Example 10 were mixed with white carbon black at a mass ratio of 4:5, and then added to natural rubber, the mass ratio of the functional rubber and plastic additives to natural rubber was 3:20, and the wear-resistant rubber material was obtained by vulcanization; the wear-resistant rubber material obtained in each group was tested for tensile strength, elongation at break, tear strength, DIN abrasion, SAR heel, SAR level, SRB heel and SRB level (wherein, SRA is the anti-slip coefficient of the sole tested on a tile coated with soap solution; SRB is the anti-slip coefficient of the sole tested on a steel plate coated with glycerol). The control group only used waste desulfurizer added to natural rubber, the mass ratio of waste desulfurizer to natural rubber was 3:20, and the rubber material was obtained by vulcanization.

[0084] like Figure 1-Figure 3 As shown, the rubber material prepared by using the functional rubber and plastic additive obtained in Example 5 has the highest tensile strength and tear strength, the smallest DIN abrasion, and the largest anti-slip coefficients, which proves that the functional rubber and plastic additive obtained in the present invention can effectively improve the mechanical properties and wear resistance of rubber and plastic materials.

[0085] The functional rubber and plastic additives obtained in Examples 5, 6, 7 and 10 were added to bisphenol A epoxy resin E-51, with a mass ratio of 3:20, and coated on the surface of Q235 carbon steel and cured. Each group of coatings was then scratched with a blade, with a scratch width of 100 μm, so that the scratches on the coating surface showed a cross shape along the diagonal line, and then an electrochemical AC impedance spectrum test was performed.

[0086] 3.5% NaCl solution was used as the corrosion medium, the frequency was set to 0.01 Hz, the amplitude was 20 mV, and the impedance value of the sample was measured for the first 6 hours after being immersed in the corrosion medium.

[0087] In the electrochemical impedance spectrum, the low-frequency impedance value is related to the corrosion activity in the inhibition defect. In this comparative experiment, the larger the low-frequency impedance value, the better the self-healing effect.

[0088] like Figure 4 As shown, the impedance of the coating prepared by using the functional rubber and plastic additive obtained in Example 10 is always higher than that of the other groups at 0.01Hz, indicating that it has started to self-repair after being immersed in the corrosive solution after scratch treatment to block the corrosion of corrosive ions. As the immersion time increases, the impedance of Example 10 and Example 6 and Example 7 groups fluctuates, but still returns to a higher impedance, but the impedance of Example 5 group has been on a downward trend, which shows that the functional rubber and plastic additives obtained in Example 10 and Example 6 and Example 7 have self-repairing properties, and the self-repairing properties of the functional rubber and plastic additive obtained in Example 10 are better than those of Example 6 and Example 7.

[0089] The applicant believes that this is because the polar functional groups of lignin can combine with the terminal carboxyl polyamide amine through hydrogen bonding to form a dendritic structure on the surface of lignin, which not only promotes the high uniformity of the dispersion of the waste desulfurizer, but also forms a coordination bond with the waste desulfurizer on its surface. When it is used in rubber and plastic materials, it can not only enhance the tensile strength and tearing performance, but also give the material self-repairing properties. The present invention uses polyaspartic acid and carbon black for ball milling, which can not only effectively promote the breakage of carbon black agglomerates, but also polyaspartic acid can be combined with the surface of carbon black, which can effectively enhance its steric hindrance, and can form hydrogen bonds with the aforementioned activated lignin, which can further improve the wear resistance and achieve a dual self-repairing effect.

[0090] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. Ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives, characterized by: The raw materials include: waste desulfurizer, surfactant, lignin modifier, and reinforcing agent; the mass ratio of the waste desulfurizer, surfactant, lignin modifier, and reinforcing agent is 100:5-15:10-20:5-10; The lignin modifier is activated lignin; the activated lignin is prepared by the following operation: the carboxyl-terminated polyamidoamine and lignin are mixed evenly, stirred at 120-140° C. for 5-15 minutes, cooled to room temperature, and crushed; The mass ratio of carboxyl-terminated polyamidoamine to lignin is 1-2:5-10; The reinforcing agent is prepared by the following operation: carbon black N234 and polyaspartic acid are mixed and ball-milled, mixed with polyoxyethylene lauryl ether, added into water, stirred for 10-30 minutes, filtered, washed with water, vacuum dried, and crushed.

2. The ultrafine, highly dispersed, self-regenerating and recycling functional rubber and plastic additive according to claim 1, characterized in that: The waste desulfurizing agent is obtained by using a metal iron oxide type desulfurizing agent to carry out gas desulfurization and purification.

3. The ultrafine, highly dispersed, self-regenerating and recycling functional rubber and plastic additive according to claim 2, characterized in that: The sulfur capacity of the metal iron oxide type desulfurizer is 15-20%; The metal iron oxide type desulfurizer includes, by mass percentage, 25-35% calcium sulfate, 2-3% magnesium oxide, 2-5% silicon dioxide, and the balance is iron oxide.

4. The ultrafine, highly dispersed, self-regenerating and recycling functional rubber and plastic additive according to claim 1, characterized in that: The surfactant is carboxymethyl cellulose.

5. A method for producing ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additives as claimed in any one of claims 1 to 4, characterized in that: The method comprises the following steps: adding waste desulfurizer, surfactant and water into a reactor, heating to 70-90°C, maintaining the pressure of the reactor at 0.8-1.2MPa, and maintaining the temperature and pressure for 110-130 minutes; then adding a lignin modifier, and continuing to maintain the temperature and pressure for 3.5-4.5 hours; and then adding a reinforcing agent and mixing evenly.

6. A method for using the ultrafine, highly dispersed, self-regenerating and recycling functional rubber and plastic additive according to any one of claims 1 to 4, characterized in that: The ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additive as claimed in any one of claims 1 to 4 is added to the rubber and plastic polymer material and mixed evenly, and the mass ratio of the ultrafine highly dispersed self-regenerating and recycling functional rubber and plastic additive to the rubber and plastic polymer material is 15-20:100.

Citation Information

Patent Citations

  • High heat polycarbonate compositions, methods for the preparation thereof, and articles derived therefrom

    CN101466788A

  • Iron oxyhydroxide modified active carbon desulfurizer as well as preparation method thereof

    CN103521195A

  • Biomass and coal conversion technology

    CN109536195A

  • Dry desulfurization agent and preparation method thereof

    CN111974210A

  • Solid dispersion, preparation method therefor, chain-extended polyurethane using same, and epoxy resin composition comprising same

    CN112105680A